Desenvolvimento rurbano: estudo de caso do programa ligue os pontos - Carmo, Vinicius Oliveira do (2021)
Academic research in urban agriculture, rural development and sustainability has driven changes in approach to urban planning in relation to peri-urban and rurban areas. In São Paulo, urban growth in rural areas puts water resources and the city's climate balance at risk. In this dissertation, a descriptive analysis of Connect the Dots is presented, a project awarded by the Bloomberg Philanthropies Foundation, and it constitutes a focal public policy that seeks to reconnect rural producers to supply chains, encouraging them to carry out organic conversion. When producers come into contact with Connect the Dots, they are encouraged and instructed to carry out sustainable activities, offering reinforcement against urban sprawl and defending areas that fulfill important roles in the regulation of environmental and climate services. The research is developed through a case study with triangulation of evidence sources. We conclude that the reinsertion of the rural category in the reform of the Master Plan in 2014 made it possible to create new instruments for urban development, in which Ligue os Points had a defining role.